APLIKASI WEB MOBILE ANDROID SISTEM ORDER BUAH PADA PT. SENTRA MULIA ANDROID MOBILE WEB APPLICATION SYSTEM IN ORDER FRUIT ON PT. SENTRA MULIA (Information Technology and Telematics, 2015)
Abstract -- At PT.Sentra Mulia , office fruit distributor who has regular customers , to get information and reservations still via SMS / Phone , it is less effective to obtain information about the list price and the amount of stocks available . And the need for other alternatives that can enable customers still get the latest information about the products that will be in the message , which will facilitate the ordering process . Building and designing a web -based application fruit bookings mobile android is another alternative to overcome these problems , in making this application using PHP programming language and Java , while for the database used is MySQL , which is used as a launcher android in running applications that allows users to access the application on android smartphone . System development method in use is the Prototype Model . This application focuses on user ( regulars ) and admin . Features that can be accessed by regulars after login which could see the price list information , the latest stock and ordering process. Results of this research is the presence of a web -based application fruit bookings mobile android on PT . Sentra Mulia which can facilitate a regular customer to place an order fruit , fruit see the latest stock prices . Assist in providing reservation service with good fruit , helping increase the number of transactions that take place so as to increase the company's revenue  Keywords: booking, PHP, mobile web android